Streneous exercise increases plasmatic and urinary Leukotriene E4 in cyclists - Caillaud, C.; Le Creff, C.; Legros, P.; Denjean, A. (Canadian Journal of Applied Physiology, 2003)
The purpose of this study was to investigate plasma and urinary levels of leukotriene (LT) and the changes in pulmonary function induced by strenuous exercise in highly trained cyclists (HT) with mild exercised-induced hypoxemia (EIH). Method: Nine HT and five untrained subjects (UT) performed a 30-min exercise at 78% of their VO2peak. Leukotriene E4 (LTE4) was assayed in plasma and urine. Pulmonary function tests and pulmonary diffusion capacity (DLCO) were examined before and after exercising. Ear arterialized blood gases were assessed at rest and during exercise. Results: The mean drop in partial oxygen pressure was 15 mmHg in HT during exercise; and the DLCO decreased by 7.5% following exercise. No significant changes were found in forced vital capacity or forced expiratory flows. LTE4 levels increased significantly in HT following exercise: urinary LTE4 was 42.9 ± 6.3 ng·mmol-1 creatinine at rest and 66.3 ± 11.9 ng·mmol-1 creatinine 2 hrs after exercise, and plasma LTE4 rose from 528 ± 91 pg·mL-1 at rest to 897 ± 123 pg·mL-1 after exercise. By contrast, urinary LTE4 level was unchanged in the UT group. Among the HT group, there was no significant correlation between urinary LTE4 changes and PO2, air flow rates, or DLCO changes. Conclusion: These results suggest that strenuous exercise induces an increase of LTE4 release in highly trained cyclists with mild EIH. These changes in LTE4 levels were not related to significant impairment of lung function.